A Study of Factors Affecting on Brass Clay Forming Process by Sculping - Jutilatptavorn, Anuwat; Jamwong, Parichat; Saejear , Kultida (Srinakharinwirot University Engineering Journal, 2023)
This research aimed to study the factor affecting the brass clay forming process by sculpting and applies with the method of factorial design of experiment and using the statistical program to analyze and transform the result to find the optimal conditions for forming brass clay. The study starts with learning about controllable factors. The four independent variables were the type of binders, percentage of binders used in mixing, temperature and duration of sintering. The results of physical and mechanical properties obtained were analyzed and sorted the optimal condition to select the most optimal condition for forming the brass clay. It was found that the most optimal condition for forming by sculpting is carboxymethylcellulose 1% sintered at 900 Celsius for 1 hour. This condition has volume shrinkage after forming about 0.76%. The physical characteristics of workpieces after forming and removing the binder have good stability, no separation of layers or cracks. After sintering, the workpiece has completely combined and the volume shrinkage was 17.4%. The density was 5.31 and the surface hardness was 37.73 HV. The result of applying the aforementioned conditions by sculpting shows that the clay has the flexibility and be able to sculpt to any shape easily. Besides, it can be applied together with stamping, cutting, rolling, patching and forming.